Education 4.0: Online Learning Management Using Education Smart Courses - Mehta, Silpha; Magdalena, Lena (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2022)
The number of students at tertiary and domestic universities rises as a result of evolving educational practices.However, in several Indonesian universities, this development has not been matched by an equalization of the course digitization system that can form soft skills and hard skills. As a result, there are gaps for instructors and students who want to form skills in these areas. Education Smart Courses (E-Scores) can solve the issues in education that arise when courses are gamified by developing a platform using sophisticated blockchain technology.The business model method of CANVA and TKT was then used in this study to systematically measure technological development.The advantages of Education Smart Courses (E-Scores), Blockchain-based innovations that academics can easily access, and gamification in educational courses, with the hope that prototypes will become more valuable and be developed in order to be able to provide better change.